The 'Quiet Eye' and motor performance in basketball free throw shooting - Ece Ayaz Kanat; Deniz Şimşek (Physical Education of Students, 2021)
Background and Study Aim. This study investigates expert and amateur basketball players' visual tracking strategies accuracy and inaccuracy free throws.